2002
DOI: 10.1017/s0030605302000091
|View full text |Cite
|
Sign up to set email alerts
|

The decline and conservation management of the threatened endemic palms of the Mascarene Islands

Abstract: The conservation status of the five genera and 11 species of palm endemic to the Mascarene Islands (Mauritius, La Réunion and Rodriques) are reviewed. All species are threatened with extinction; nine taxa are classified as Critically Endangered and four as Endangered on the 2000 IUCN Red List. Two taxa survive as single wild specimens (Hyophorbe amaricaulis and Dictyosperma album var. conjugatum); an additional seven taxa have wild populations of 100 or fewer. Although the historical phase of large-scale fores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…Their study recorded that seed predation, goat grazing, pig damage and human harvesting were contributing to the lack of regeneration (Chapin et al 2007). Maunder et al (2002) reported that high levels of seed predation of endangered Mascarene Island palms were preventing natural regeneration, and that active enhancement programs were needed to overcome this problem. Where there was grazing, Ford et al (2008) observed a lack of recruitment of seedlings to larger class sizes in L. carinensis.…”
Section: Population Viabilitymentioning
confidence: 97%
See 1 more Smart Citation
“…Their study recorded that seed predation, goat grazing, pig damage and human harvesting were contributing to the lack of regeneration (Chapin et al 2007). Maunder et al (2002) reported that high levels of seed predation of endangered Mascarene Island palms were preventing natural regeneration, and that active enhancement programs were needed to overcome this problem. Where there was grazing, Ford et al (2008) observed a lack of recruitment of seedlings to larger class sizes in L. carinensis.…”
Section: Population Viabilitymentioning
confidence: 97%
“…For example, in a case study of threatened Pritchardia species in Hawaii, Chapin et al (2004) advocate conservation of existing populations, establishing ex situ populations and reintroducing plants into the wild. On the Mascarene Islands seven palm taxa have populations of 100 or fewer mature individuals in the wild and an active recovery involving both in-situ and exsitu approaches has been recommended to prevent extinction (Maunder et al 2002). Dowe et al (1997) also indicated that recovery of Carpoxylon macrospermum required active conservation programs to establish new populations containing the range of genetic diversity found in the species.…”
Section: Restorationmentioning
confidence: 99%
“…& Drude var. conjugatum H. E. Moore & J. Guého); an additional seven taxa have wild populations of 100 or fewer (Maunder et al 2002). Some of these taxa have benefited from recent conservation efforts but a lot has to be done to save the rest of the species that are on the verge of extinction.…”
Section: Embryo Rescue and Conservation Of Palmsmentioning
confidence: 98%
“…Eleven species of palms that are endemic to the Mascarenes are threatened according the IUCN statistics. All species are threatened with extinction; nine taxa are classified as CR and four as Endangered (EN) in the 2000 IUCN Red List (Maunder et al 2002). Two taxa survive as single wild specimens (Hyophorbe amaricaulis Mart.…”
Section: Embryo Rescue and Conservation Of Palmsmentioning
confidence: 99%
“…Juvenile recruitment is thus severely impacted by seed predation in L. mooreana. Several species of palm have been reported to be threatened with extinction from lack of regeneration due to seed or seedling predation (Maunder et al 2002;Henderson et al 2006) and all palm species on LHI are affected. Despite the large numbers of seeds produced, heavy predation by rats will lead to reduced numbers for selection to act and a reduced capacity of L. mooreana to respond to episodic recruitment events.…”
Section: Reproduction Inbreeding and Climate Changementioning
confidence: 99%